NATURAL CONVECTION IN ICE MELTING FROM BELOW. - Yen,Yin-Chao (1966)
An experimental technique was successfully developed to study the effect of natural convection (thermal instability) on the melting rate of ice. Reproducible results were obtained by using homogeneous, bubble-free ice samples for the melting process. The problem of volume change due to phase transition or separation of the ice-water interface encountered when melting from below was solved by continuously adding water at the same temperature as the constant temperature bath which supplied the heat for melting. Under certain temperature conditions irregularities in the interface, a result of convective motion, became very apparent and could be observed visually. By periodically measuring the amount of water added and varying the initial temperature of the ice sample T sub zero and that of the heat source T sub s extensive results were obtained demonstrating the effects of these temperatures on the melting rate which could be expressed in terms of dimensionless parameters. (Author)